PHYSICAL ATTRIBUTE OF NEAT SEMEN AND OXIDATIVE STRESS PARAMETERS OF SEMINAL PLASMA OF JAFFARABADI BUFFALO BULLS - CHAVDA, B P; VALA, K B; SOLANKI, G B; SINGH, V K; PARMAR, K H (The Indian Journal of Animal Reproduction, 2021)
The present study was undertaken during summer season on four mature Jaffarabadi buffalo bulls at the Cattle Breeding Farm, JAU, Junagadh, from March to June, 2021. A total of 24 semen ejaculates (6 ejaculates/bull) collected by AV method were evaluated for physical characteristics and oxidative stress parameters, viz., lipid peroxidation (LPO/MDA) and GST enzyme activity in seminal plasma using standard procedures and assay kits on an autoanalyzer. The mean values of fresh semen characteristics observed were ejaculate volume 4.03±0.38 ml, sperm concentration 1464±82.05 x106/ml, mass motility score 3.79±0.08, individual motility 90.00±0.52%, live sperm 92.04±0.59%, total sperm abnormalities 4.50±0.22%, intact acrosome 87.08±0.58%, and HOS reacted sperm 83.00±0.49 %. Among all the parameters studied, only the sperm concentration and sperm morphological abnormalities varied significantly (P<0.05) between bulls. The mean values of LPO and GST activities in fresh seminal plasma were 6.84±1.76 μM MDA and 18.64±1.34 nmol CDNB /ml/min, respectively, without significant variation between bulls. Overall, the semen picture and oxidative markers were within the normal physiological range of the species.